1998
DOI: 10.1172/jci4221
|View full text |Cite
|
Sign up to set email alerts
|

A critical role for transforming growth factor-beta in donor transfusion-induced allograft tolerance.

Abstract: Donor-specific (DST) or nonspecific blood transfusions administered before transplantation can enhance survival of vascularized allografts both in humans and animals but the immunological mechanisms of this effect remain unclear. We have analyzed the expression and the role of endogenous TGF-␤ 1 in a model of heart allograft tolerance, induced by pregraft DST in adult rats. We reported previously that this tolerance occurs despite a strong infiltration of leukocytes into the graft that are unable to produce bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

6
122
0
1

Year Published

1999
1999
2001
2001

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 150 publications
(129 citation statements)
references
References 51 publications
6
122
0
1
Order By: Relevance
“…1,2 In certain tolerance protocols, such as the one induced by donor blood transfusion, expression of both Th1 and Th2 cytokines is inhibited in tolerated grafts as compared with levels observed in rejected ones. 3 In this and in other models of tolerance, expression of TGF-␤1 has been clearly implicated in the establishment of tolerance. 3,4 Furthermore, IFN-␥ and TGF-␤1 seem reciprocally to regulate pro-and compared with Addl324-treated (9.3 ± 3.3 days) or untreated groups (7.8 ± 1.5 days).…”
mentioning
confidence: 77%
See 4 more Smart Citations
“…1,2 In certain tolerance protocols, such as the one induced by donor blood transfusion, expression of both Th1 and Th2 cytokines is inhibited in tolerated grafts as compared with levels observed in rejected ones. 3 In this and in other models of tolerance, expression of TGF-␤1 has been clearly implicated in the establishment of tolerance. 3,4 Furthermore, IFN-␥ and TGF-␤1 seem reciprocally to regulate pro-and compared with Addl324-treated (9.3 ± 3.3 days) or untreated groups (7.8 ± 1.5 days).…”
mentioning
confidence: 77%
“…3 In this and in other models of tolerance, expression of TGF-␤1 has been clearly implicated in the establishment of tolerance. 3,4 Furthermore, IFN-␥ and TGF-␤1 seem reciprocally to regulate pro-and compared with Addl324-treated (9.3 ± 3.3 days) or untreated groups (7.8 ± 1.5 days). Immunohistochemical analysis of allografts after gene transfer of IL-10 showed that leukocyte infiltration was quantitatively equivalent to that seen in control groups but with a strong tendency towards lower levels of CD8 + cells.…”
mentioning
confidence: 77%
See 3 more Smart Citations